Kontrak Kerja Pada PT. Primatexco Indonesia Batang dalam Perspektif Hukum Ekonomi Syariah - jumailah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This present study aims to explain the perspectives of sharia economic law on the contract of employment at PT Primatexco Indonesia, Batang. The Law Number 13 of 2003 on Manpower constitutes the protection of labor that is intended to guarantee the basic rights of workers/labor. The emergence of the Law is expected to be able to realize the welfare of workers/labor as well as their families by paying great attention to the development and growth of business. It was field research by employing a qualitative study design, and the setting was at PT. Primatexco Indonesia, Batang. The research findings promote that even though there has been the Law concerning Manpower, this law has not run in accordance with the stipulated rules. It illustrates that the content of the Law has not accommodated the stipulation of the existing Law yet, and even the content is sometimes unclear, which is stated in the Article 54 of the Law on Manpower. The fiqh (Islamic jurisprudence) scholars agree that a contract possesses the force of law caused by syara’ (Islamic law), instead of the actions performed by the two parties make the contract. Likewise, the actions play a role as a cause for the effect of the contract. It suggests that no one is not able to do arbitrarily in terms of the requirements they provide in the contract of employment so that all people’s actions are based on the law of Allah.